PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 PARIAMAN - Nabila, Sri Falyra (Departemen Matematika, 2023)
One of the ability needed to help students learn mathematics is mathematical communication ability. However, class VIII students of SMPN 3 Pariaman still have low mathematical communication ability. This is because students' mathematical communication ability have not increased using conventional learning models that have been used so far. The pair check cooperative learning model is considered a model that can overcome this problem. The static group research design was used with a quasi-experimental research type. Simple Random Sampling is used to perform the sampling procedure. Quizzes and tests of mathematical communication ability are the instruments used. T test is then used to test the hypothesis. The results of data analysis show that the P-value is 0.000, which means rejecting H0. Thus it can be concluded that class VIII students of SMPN 3 Pariaman who study with the pair check model are better than conventional learning models. Keywords. – Mathematical Communication Abilities, Cooperative Learning, Pair Check